From labor to reward : black church beginnings in San Francisco, Oakland, Berkeley, and Richmond, 1849-1972 - Taylor, Martha C. (Church historian) (Resource Publications, 2016)
From Labor to Reward is a pioneering, epic, and groundbreaking book that fills a huge void in American religious history, black religious history, and traditions of the black church. Until now, no other book has chronicled the rich religious experiences of black church beginnings in the Bay Area. Martha C. Taylor provides penetrating insight into the early makings of the black church in the Bay Area. With attention to detail, Taylor captures the joys, frustrations, and unity of black people who left the segregated Deep South, came to the Bay Area seeking freedom only to face similar adversities of segregation, racism, housing discrimination, KKK threats of violence, and other socio-political barriers. Remarkably, these early pioneers brought their culture, traditions, and experiences from the South and built a strong vibrant religious community. From Labor to Reward speaks for the legacy of African Americans who were gospel social activists using the church as the anchor. Multiple sources of research and interviews were gathered from church records, newspaper clippings, and other written sources to tell this unknown story. This book is sure to be a classic and a must read for all persons interested in history. (Publisher).